Design of Medium Access Control Protocol for IEEE 802.15.4 Based WSNS to Reduce Collisions and Prevent Simultaneous Data Transmission by Nodes - Saha, Sumit; Dumka, Ankur; Dimri, Priti (International Journal of Computer Sciences and Engineering, 2019)
Collisions which occur in a channel during data transmissions result in re-transmissions and this causes energy dissipation. In order to reduce this effect, a new Medium Access Control (MAC) Protocol is designed. In this paper, the existing and current mechanisms of WSNs have been studied and their shortcomings identified. Accordingly the design parameters of IEEE 802.15.4 CSMA/CA based WSNS hse been extended and a new design parameter has been evolved which reduces the collisions and prevents simultaneous data transmission by nodes. This paper suggests minor modifications to the current mechanism of IEEE 802.15.4 CSMA/CA by incorporating re-transmission limits of the nodes with packet collision probability.